An analysis of the roles played by Born’s rule, Bell’s theorem and Bohr’s complementarity in the establishment of the quantum-classical boundary - De Zela Martínez, Francisco (Pontificia Universidad Católica del Perú, 2018)
This work contains a series of contributions that are related, in one form or another, with the placement of the quantum-classical boundary. Three results that have been widely taken as characteristic traits of quantum phenomena are here shown to appear in purely classical contexts as well. These are: Born’s rule, Bell violations and Bohr’s complementarity. This work discusses how Born’s rule may be derived from some basic assumptions that relate to measurements in general, thereby showing that said rule applies when dealing with both classical and quantum cases. Bell violations are ultimately based upon Born’s rule. Therefore, the applicability of the latter in a classical context leads to Bell violations in this very same context. We can therefore predict non-quantum Bell violations. Moreover, we report experimental results confirming these violations. Finally, we address Bohr’s complementarity in a quantitative way and derive an equation that links visibility and distinguishability – two complementary features of an interferometric array – with polarization, which can be seen as an “internal” degree of freedom.

Este trabajo contiene una serie de contribuciones que están relacionadas, de una forma u otra, con la ubicación de la frontera clásico-cuántica. Se muestra en él cómo aparecen también en contextos puramente clásicos tres resultados que han sido ampliamente aceptados como característicos de los fenómenos cuánticos. Estos resultados son: la regla de Born, las violaciones de Bell y la complementariedad de Bohr. El presente trabajo discute cómo se puede derivar la regla de Born a partir de suposiciones básicas que están relacionadas a las mediciones en general, mostrando así que dicha regla es aplicable a los casos clásico y cuántico. Las violaciones de Bell tienen por base la regla de Born. Por ello, la aplicabilidad de esta última en el contexto clásico lleva a violaciones de Bell en ese mismo contexto. Podemos así predecir violaciones de Bell no cuánticas. También se incluye resultados experimentales que confirman las citadas violaciones. Finalmente, se aborda la complementariedad de Bohr en forma cuantitativa y se deriva una ecuación que vincula visibilidad y distinguibilidad – dos aspectos complementarios de un arreglo interferométrico – con polarización, la cual puede ser vista como un grado de libertad “interno”.
Keywords: Teoría cuántica; Interferometría; Polarización; https://purl.org/pe-repo/ocde/ford#1.03.00